2016
DOI: 10.1051/0004-6361/201527403
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric evaporation flows and density changes deduced from Hinode/EIS during an M1.6 flare

Abstract: Aims. We study the response of the solar atmosphere during a GOES M1.6 flare using spectroscopic and imaging observations. In particular, we examine the evolution of the mass flows and electron density together with the energy input derived from hard X-ray (HXR) in the context of chromospheric evaporation.Methods. We analyzed high-cadence sit-and-stare observations acquired with the Hinode/EIS spectrometer in the Fe xiii 202.044 Å (log T = 6.2) and Fe xvi 262.980 Å (log T = 6.4) spectral lines to derive tempor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 82 publications
1
9
0
3
Order By: Relevance
“…No caso de determinações a partir de observações no ultravioleta, a velocidade estimada tem a mesma ordem de grandeza das velocidades Doppler do material ascendente, entre 250 e 300 km/s, obtidas por Gömöry et al (2016), para fluxo de plasma ascendente registrado durante a fase de declínio de um flare solar analisado e da velocidade aparente dos fluxos ascendentes de 50 a 630 km/s, com valor médio de ~170 km/s, obtidos por Zhang et al (2019), reforçando as considerações de que as emissões métricas associadas a flare, apresentando lenta taxa de deriva, podem representar assinatura do processo de evaporação cromosférica que ocorre em regiões da coroa solar.…”
Section: Consideraçôes Finaisunclassified
See 2 more Smart Citations
“…No caso de determinações a partir de observações no ultravioleta, a velocidade estimada tem a mesma ordem de grandeza das velocidades Doppler do material ascendente, entre 250 e 300 km/s, obtidas por Gömöry et al (2016), para fluxo de plasma ascendente registrado durante a fase de declínio de um flare solar analisado e da velocidade aparente dos fluxos ascendentes de 50 a 630 km/s, com valor médio de ~170 km/s, obtidos por Zhang et al (2019), reforçando as considerações de que as emissões métricas associadas a flare, apresentando lenta taxa de deriva, podem representar assinatura do processo de evaporação cromosférica que ocorre em regiões da coroa solar.…”
Section: Consideraçôes Finaisunclassified
“…Com o avanço da tecnologia e aprimoramento dos instrumentos de observação solar, principalmente a bordo de satélites, como o Interface Region Imaging Spectrograph (IRIS) e o Extreme-ultraviolet Imaging Spectrometer (EIS), uma série de estudos do fenômeno da evaporação cromosférica tem sido realizada a partir de dados de linhas espectrais no extremo ultravioleta e deslocamento Doppler. Entre esses trabalhos, podem ser citados, Li et al (2019); Li et al, (2015); Gömöry et al (2016); Li et al (2017a); Li et al, (2017b); Brosius e Inglis (2017); Lee et al (2017) e Gupta, Sarkar e Tripathi (2018); Sadykov et al (2019). A evaporação cromosférica também tem sido estudada a partir de imagens e dados do arranjo de telescópios Atmospheric Imaging Assembly (AIA), abordo do Solar Dynamics Observatory (SDO) (ZHANG et al, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…As most of the flare energy is deposited in the chromosphere, a strong evaporation of the heated plasma occurs (e. g., Neupert 1968;Fisher et al 1985a,b,c;Graham & Cauzzi 2015). A detailed EUV spectroscopic analysis of explosively evaporating plasma following an M1.6-class flare by Gömöry et al (2016) found electron densities up to 3.16 × 10 10 cm −3 at a temperature of 1.56 MK. The evaporation provides an injection of plasma into flare coronal loops (hereafter flare loops) and leads to the formation of bright high-density structures at the apex of the flare loop arcade.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the energy deposition profile is a key element in determining the response of the solar atmosphere to flare heating (Mariska et al 1989;Allred et al 2015) and hence in interpreting the plethora of observations of Doppler-shifted and -broadened spectral lines (e.g., Antonucci et al 1982;Emslie & Alexander 1987;Doschek 1990;Mariska et al 1993;Bentley et al 1994;Rilee & Doschek 2001;Landi et al 2003;Brosius & Phillips 2004;Li et al 2015a,b;Milligan 2015;Reep et al 2015;Tian et al 2015;Brosius et al 2016;Brosius & Inglis 2017;Gömöry et al 2016;Polito et al 2016;Warren et al 2016;Kontar et al 2017;Li et al 2017) in terms of the velocity differential emission measure (Newton et al 1995) corresponding to candidate energy transport models. In this paper we therefore build on the results of Bian et al (2017) to derive a formula for the energy deposition profile associated with the passage of electrons through a cold target, where diffusion associated with angular scattering is explicitly taken into account.…”
Section: Introductionmentioning
confidence: 99%